Efficiency of Village Government Administration Information System Applications in realizing Public Information Openness - Putri, Amanda; Taufiq, Ahmad; Swasanti, Ida (Universitas Muhammadiyah Gorontalo, 2023)
The Bojonegoro Regency Government, which is overseen by the Bojonegoro Regency Community and Village Empowerment Service, initiated the creation of the Village Government Administration Information System Application (SIAP DESA). This application can be freely accessed by the public, however, it was discovered that in its implementation the village SIAP application was not completely efficient. Based on initial observations, it was found that many villages had not completed the information in the village SIAP Application. The aim of this research is to determine the efficiency of the Village SIAP Application in realizing public information transparency. The method used is a descriptive qualitative approach with data collection through interviews, observation and documentation. The research results show that the village SIAP application is not completely efficient. Several factors that underlie this include the Village SIAP Application, there is a menu that has no time limit for uploading files, namely the data menu for the Village Head, Village Apparatus, PAW Members and Legal Products. Furthermore, there is also no time limit for completing data updating, making each village feel more relaxed in updating data in the application. The government's digital update in building the village SIAP application is the right step for efficiency, especially in terms of materials and costs. However, the SIAP Village Application can be said to be fully efficient if the menus are complete, accurate and updated. Therefore, it is important to create a timeline for updating the Village SIAP Application menus to show openness of public information to the community and related stakeholders.